The effect of increasing heel height on lower limb symmetry during the back squat in trained and novice lifters - Sayers, M. G. L.; Hosseini Nasab, S. H.; Bachem, C.; Taylor, W. R.; List, R.; Lorenzetti, S. (BMC Sports Science, Medicine and Rehabilitation, 2020)
Background: Symmetry during lifting is considered critical for allowing balanced power production and avoidance of injury. This investigation assessed the influence of elevating the heels on bilateral lower limb symmetry during loaded (50% of body weight) high-bar back squats. Methods: 'Ten novice (mass 67.6 ± 12.4 kg, height 1.73 ± 0.10 m) and ten regular weight trainers (mass 66.0 ± 10.7 kg, height 1.71 ± 0.09 m) were assessed while standing on both the flat level floor and on an inclined board. Data collection used infra-red motion capture procedures and two force platforms to record bilateral vertical ground reaction force (GRFvert) and ankle, knee and hip joint kinematic and kinetic data. Paired t-tests and statistical parametric mapping (SPM1D) procedures were used to assess differences in discrete and continuous bilateral symmetry data across conditions. Results: Although discrete joint kinematic and joint moment symmetry data were largely unaffected by raising the heels, the regular weight trainers presented greater bilateral asymmetry in these data than the novices. The one significant finding in these discrete data showed that raising the heels significantly reduced maximum knee extension moment asymmetry (P = 0.02), but in the novice group only. Time-series analyses indicated significant bilateral asymmetries in both GRFvert and knee extension moments mid-way though the eccentric phase for the novice group, with the latter unaffected by heel lift condition. There were no significant bilateral asymmetries in time series data within the regular weight training group. Conclusions: This investigation highlights that although a degree of bilateral lower limb asymmetry is common in individuals performing back squats, the degree of this symmetry is largely unaffected by raising the heels. Differences in results for discrete and time-series symmetry analyses also highlight a key issue associated with relying solely on discrete data techniques to assess bilateral symmetry during tasks such as the back squat.